The influence of immobilisation and peptide structure on the bioactivity of model antimicrobial peptides - Lourens, Gertrude Dorothy (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.